Why Put ‘Class’ in the Creative Class? - Mo, Aaron (Quaestiones Geographicae, 2012)
This paper pinpoints the problematic use of grouping creative people as a social class. Observations of the ‘creative clusters’ in Lower East Side (New York) and Islington Mill (Manchester) are used to illustrate this point. Instead, creative actors should be seen as a unique blend of work practices, and have different philosophical and aesthetic appreciation of art, which in turn influences their spatial and geographical consumption patterns inside a building and/or city. This observation questions the use of ‘class’ in Richard Florida’s (2002) The rise of the Creative Class, and consequently asks if place-making practitioners should adopt one-size-fits-all creative policies